For your own good [large type] - Downing, Samantha (Thorndike Press large print basic, 2021)
"Teddy Crutcher has won Teacher of the Year at the prestigious Belmont Academy, home to the best and brightest. He says his wife couldn't be more proud--though no one has seen her in a while. Teddy really can't be bothered with a few mysterious deaths on campus that are looking more and more like murder, or the student digging a little too deep into Teddy's personal life. His main focus is pushing these kids to their full academic potential. All he wants is for his colleagues--and the endlessly meddlesome parents--to stay out of his way. If not, well, they'll get what they deserve. It's really too bad that sometimes excellence can come at such a high cost"--Page 4 of cover.